663 First Seizure as Late Presentation of Velo-Cardio-Facial Syndrome. (October 2012) - Simão, I; Lourenço, T; Lopes, L; Ramos, MP
Abstract : Congenital hypoparathyroidism caused by Velo-Cardio-Facial Syndrome (VCFS) typically presents with hypocalcemia usually associated with other characteristic findings. It is most often diagnosed during the neonatal period. We report the case of a boy who presented with symptomatic hypocalcemia (serum total calcium 5.1mg/dL; ionized calcium 0.65mmol/L) at 8 years of age; he had a history of velopharyngeal incompetence and late development with language impairment; at presentation, mild dysmorphic facial features were detected. The laboratory evaluation revealed parathormone (PTH) < 1.0 pg/ml. The presence of hypoparathyroidism suggested VCFS, confirmed by Fluorescence in situ hybridization study that revealed a deletion on chromosome 22q11.2 zone. Therapy with calcium was undertaken at first by intravenous infusion and orally afterwards; high levels of calcium were needed to normalize serum calcium. Molecular evaluation of the parents showed no deletion in the 22q11.2 zone, allowing for the diagnosis of a de novo deletion in the index case. The importance of this report relies on the fact that the patient, despite clinical suspicions of VCFS, remained asymptomatic until late childhood, presenting with no renal dysfunction, immunological abnormalities or cardiac malformations. Considering this hypothesis and making an early diagnosis is important both for implementing timely clinical evaluation and dietary supplementation if needed and for family planning.